Engineering of Biodegradable and Excretable Inflammation‐Resolving Materials. (3rd August 2022) - Wu, Peng; Gao, Mingjie; Zhang, Chunfan; Li, Chenwen; Li, Gang; Yan, Xinhao; Lai, Xiaodan; Zhang, Yang; Zhang, Jianxiang
Abstract: Uncontrolled or chronic inflammation contributes to the pathogenesis of many acute/chronic diseases, such as acute organ injury, COVID‐19, and atherosclerosis. Intrinsically bioactive materials are promising for regulating the response magnitude and duration of inflammation, but their translation remains challenging. Herein, the engineering of a series of inflammation‐resolving materials by rationally integrating different functional modules into a hydrolyzable scaffold is reported. The obtained functional materials can assemble into potent anti‐inflammatory micelles capable of eliminating different types of reactive oxygen species, releasing bioactive molecules, and simultaneously hydrolyzing into water‐soluble and excretable compounds. Cellularly, these micelles effectively inhibit the migration, activation, and production of molecular mediators in inflammatory cells. Benefiting from the small size and high bioactivity, the developed micelles efficiently accumulate in the kidneys of mice with acute kidney injury (AKI) and efficaciously alleviate AKI. Bioactive micelles also demonstrate desirable targeting and superior efficacies in mice with acute liver failure. Mechanistically, inhibition of oxidative damage, attenuation of inflammatory cell infiltration and activation, and promoting resolution of inflammation mainly account for beneficial therapeutic effects of micelles. Moreover, preliminary studies reveal the excellent safety of micelles. Consequently, the bioactive materials represent a new type of efficacious, safe, scalable, and affordable therapy for a broad spectrum of inflammatory diseases. Abstract : A series of inflammation‐resolving materials are engineered by integrating different functional modules into a hydrolyzable scaffold. The obtained bioactive materials can assemble into anti‐inflammatory micelles capable of eliminating reactive oxygen species, releasing bioactive molecules, and simultaneously hydrolyzing into water‐soluble and excretable compounds. By inhibiting oxidative and inflammatory responses, the micelles efficaciously alleviate acute kidney injury and acute liver failure.